The quality of gender and sex integration in scientific articles resulting from health research funded by the Brazilian Ministry of Health 2004–2016. - Batista, Rayane Cavalcante Pereira; Solans-Domènech, Maite; Angulo-Tuesta, Antonia (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: Integrating sex and gender into health research is critical to contributing to an ethical and more responsible science to address significant knowledge gaps, resulting in higher-quality evidence for all. Subject and methods: Using the Essential Metrics for Assessing Sex and Gender Integration in Health Research Proposals Involving Human Participants, we evaluate the quality of the integration of sex and gender in the 350 scientific articles produced by 144 health studies funded by the Department of Science and Technology of the Brazilian Ministry of Health between 2004 and 2016. Results: The results show that clinical research articles are the type of studies that most frequently report on sex differences, while population and public health research articles most frequently report on gender differences. Analysis of the quality of sex and gender integration reveals low levels of qualification in the items of the literature review and research objectives (section 1) and participant recruitment and retention (section 2). However, the data collection tools, data analysis, and knowledge translation (section 3) items were rated as excellent and good. Conclusion: Funding agencies and public institutions should recognize the importance of the integration of sex and gender at all stages of the research process, for instance, through awareness and training for researchers and reviewers, clear requirements, and the possibility to use metrics in the evaluations process.